Self Organizing Map (SOM) Network Application Support for Short-term Investment Decisions - Bac, Maciej (Wykorzystanie sieci (SOM) do wspomagania krótkoterminowych decyzji inwestycyjnych, 2010)
Popularity of global futures markets grows every year. Attracted by the possibility of quick and easy profits, investors increase liquidity of the base Instruments and derivatives. Liquidity growth brings a feeling of security and attraction to markets. Professional investors introduce more and more advanced techniques and tools to support analysis of financial Instruments. Computers are used not only to perform standard analysis but also to utilize artificial intelligence as a tool for prediction. This is an area where much more remains to be discovered than has already been defined, and hence the author's interest in this topic. Referring to those observations, the objective of this article is to present (and review) the concept of SOM neural network application for investment decisions support. The author has presented results of his own research based on the developed system, which is a practical attempt to verify the presented idea.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 104, s. 79-88
Keywords: neural networks; stock exchange; SOM